Chinese foreign policy an introduction - Lanteigne, Marc (Routledge, Taylor & Francis Group, 2016)
This updated and expanded new edition of Chinese Foreign Policy examines the patterns of engagement with various domestic and international actors that have shaped Beijing's foreign policy since the Cold War. It explores a series of ongoing questions and trends, as well as offering an in-depth look at the key areas of China's modern global relations